1998
DOI: 10.1046/j.1360-0443.1998.9321834.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and mortality. I. Characteristics of drinking groups

Abstract: Characteristics of two groups of abstainers, other than their non-use of alcohol, may confound the associations found between drinking and mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 2 publications
7
89
0
2
Order By: Relevance
“…Cause-specific analyses suggested that the reform was negatively associated with overall cancer, lung cancer, ischemic heart disease (for women), overall external causes (for men), and accident mortality, possibly indicating that tobacco (10,11) and alcohol (12) play a role here. However, the relationship between education and alcohol consumption is complex (13)(14)(15), and an increased risk of mortality, from lung cancer and liver cirrhosis combined, was recently reported for exposed men between 1985-2005 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cause-specific analyses suggested that the reform was negatively associated with overall cancer, lung cancer, ischemic heart disease (for women), overall external causes (for men), and accident mortality, possibly indicating that tobacco (10,11) and alcohol (12) play a role here. However, the relationship between education and alcohol consumption is complex (13)(14)(15), and an increased risk of mortality, from lung cancer and liver cirrhosis combined, was recently reported for exposed men between 1985-2005 (16).…”
Section: Discussionmentioning
confidence: 99%
“…We found nonsignificantly lower risk associated with both ''nondrinking'' and higher consumption; however, an earlier analysis of lung cancer in the same cohort suggested that nondrinkers may include ex-drinkers (35), in which case our findings may indicate an overall inverse association between alcohol and NHL. Considering the inconsistencies in the literature, no doseresponse, potential confounding by other lifestyle factors, and potential misspecification of past alcohol intake (36)(37)(38), further prospective studies with detailed alcohol intake history are warranted to estimate the risk associated with true lifetime exposure to alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, if the determinants differ, affecting the intensity of consumption will require different policy instruments from those affecting the frequency (Berggren & Sutton 1999). Drinking patterns rather than simply the average intake have been found to be of importance in the relationship between alcohol consumption and chronic conditions, as well as more subjective health indicators (Camargo 1989;Fillmore et al . 1998;San Jose et al .…”
Section: Theoretical Frameworkmentioning
confidence: 99%